Efektivitas Pengelolaan Dana Desa Dalam Meningkatkan Kesejahteraan Masyarakat Desa Kuatae Kecamatan Kota Soe Kabupaten Timor Tengah Selatan - Zethsander Djawa Liunokas; Petrus E. de Rozari; Novi Theresia Kiak (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This study aims to determine the effectiveness of village fund management in improving the welfare of the people of Kuatae Village, Soe City District, South Central Timor Regency. This research method is a case study using qualitative research methods. The focus of this study is to observe and find out the effectiveness of village fund management in improving the welfare of the kuatae village community, using data collection techniques in the form of observation, interviews and documentation. The results of this study show that the effectiveness of village fund management in improving the welfare of the people of Kuatae Village in the regulations implemented by the Kuatae village government is in accordance with applicable laws and regulations, Government performance is still not very good and knowledge of village government performance is also still low, There are still delays in issuing policies regarding village funds and changes to policies and still low knowledge and behavior of the community in managing activities in the village.